The ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK MINERAL BUKAN LOGAM DAN BATUAN TERHADAP PENDAPATAN ASLI DAERAH (STUDI KASUS PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN BUTON TENGAH): Indonesia - Muhammad Rais (Jurnal Multidisipliner Kapalamada, 2025)
Analysis Of The Effectiveness And Contribution Of Non-Metal And Rock Mineral Tax On Regional Original Revenue. This study aims to examine the effectiveness and contribution of Non-Metal and Rock Mineral Tax revenues to the Regional Original Revenue. The research employed field research and library research methods, with a descriptive data analysis approach. The results indicate that the effectiveness level of Non-Metal and Rock Mineral Tax realization during the 2022–2024 period was classified as very effective, with an average effectiveness rate of 187.76%. Specifically, the effectiveness reached 283.53% in 2022, decreased to 136.27% in 2023, and slightly increased to 143.48% in 2024. In terms of contribution to PAD, this tax demonstrated a very low performance, with an average contribution of only 6.23%. The contribution was 4.55% in 2022, increased to 5.78% in 2023, and reached 8.36% in 2024. These findings suggest that although the tax is highly effective in achieving revenue targets, its contribution to overall regional revenue remains relatively limited.